(untitled) (MCIT: Proceedings of International scientific and practical conference, 2023)
Anthropogenic factors are increasingly influencing the climate of our planet and are harmful to the environment. To control the environmental state, it is essential to conduct an inventory of greenhouse gases, analyze the spatial distribution of emission sources, and constantly monitor the amount. Since swine farming is one of most efficient Ukraine’s livestock industries, this study is dedicated to calculating methane emissions from swine enteric fermentation and determining their spatial distribution. Антропогенні чинники все більше впливають на клімат нашої планети і завдають шкоди навколишньому середовищу. Для контролю за станом навколишнього середовища необхідно проводити інвентаризацію парникових газів, аналізувати просторовий розподіл джерел емісії, постійно контролювати обсяги. Оскільки свинарство є однією з найефективніших галузей тваринництва України, це дослідження присвячене моделюванню емісії метану від кишкової ферментації свиней та визначенню їхнього просторового розподілу.